MANAJEMEN PEMASARAN PENDIDIKAN: MENINJAU PROSES PROMOSI LEMBAGA SMP IT DARUL MUTA’ALLIMIN MEULABOH - Kurniawan, Ade; Eka Safira, Nurul; Bakhtiar, Bakhtiar (Program Studi Manajemen Pendidikan Islam, 2024)
SMP IT Darul Muta'allimin, as a new institution, can attract public interest by enrolling their children in this school. Since 2017, the first year of the establishment until 2023, SMP IT Darul Muta'alimin has had an increasing number of students. The article aims to describe how SMPT IT Darul Muta'alimin carries out the institutional promotion process. This study used qualitative methods, including interviews, observation, and documentation data collection techniques. The subjects in this study were the head, Vice Principal of public relations, Vice Principal of student affairs, two teachers and five students. Analytical techniques use qualitative analysis techniques. The results showed that promotional activities began with the planning stages of institutional promotion carried out through committee work meetings that discussed the type of promotion, the amount of costs and the target area of education promotion. Education promotion activities are carried out in several forms: 1) visits to elementary schools / MIN, 2) distribution of brochures and installation of banners, 3) digital promotion through social media, 4) holding school events, 5) public relations activities, and 6) word of mouth promotion. Furthermore, promotional activities are evaluated through evaluation meetings. In the evaluation process, the team looked at the level of success achieved and the shortcomings of educational promotion activities. The lack of education promotion this year is an input for the next period of promotional activities